2003
DOI: 10.1103/physrevb.67.035413
|View full text |Cite
|
Sign up to set email alerts
|

Helium atom scattering studies of the structure and vibrations ofH2physisorbed on MgO(001) single crystals

Abstract: The surface structure and vibrations of normal-H 2 , para-H 2 , HD, and normal-D 2 films physisorbed on in situ cleaved single crystal MgO͑001͒ surfaces, have been investigated at surface temperatures 7-12 K using high-resolution helium atom scattering. The He-diffraction patterns agree with the sequence of c(2ϫ2)c(4ϫ2)-c(6ϫ2) structures previously determined by neutron scattering. For the H 2 monolayer three different adsorbate frequencies, two Einstein modes around 10 meV and a dispersive mode between 2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 79 publications
(106 reference statements)
4
38
0
Order By: Relevance
“…There have been a number of relevant studies on the adsorption of molecular hydrogen on MgO [1][2][3][4]. Thermodynamic studies suggest that a number of layering transitions and other less well-identified phase changes (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…There have been a number of relevant studies on the adsorption of molecular hydrogen on MgO [1][2][3][4]. Thermodynamic studies suggest that a number of layering transitions and other less well-identified phase changes (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…The formation of physisorbed monolayers of H 2 , HD, and D 2 on ionic crystal surfaces is of a particular interest, over the last 20 years [1][2][3][4], since these species in condensed phase show some quantum behavior, and are considered as a method for chemical or isotopic separation [5,6]. In addition, H 2 and D 2 monolayers on ionic crystal surfaces allow us to study ordering phenomena and phase transitions in quantum systems.…”
Section: Introductionmentioning
confidence: 99%
“…Note that there are two negative peaks at ~330 °C and ~400 °C in the H2-TPR profiles of the MgO, 0.2%Co/MgO, 0.5%Co/MgO and 1.0%Co/MgO catalysts, which could be attributed to the release of H2 adsorbed on the catalyst surface, because MgO is an excellent hydrogen storage material [55]. When the Co loading was ≤1.0%, the Co3O4 reduction peaks could not be observed, which is probably because the amount of hydrogen released from MgO is much greater than the amount of hydrogen consumed for the Co3O4 reduction.…”
Section: Redox Property (H2 Temperature-programmed Reduction (H2-tpr)mentioning
confidence: 97%